2020
DOI: 10.15763/issn.2470-9670.2020.v4.i1.a54
|View full text |Cite
|
Sign up to set email alerts
|

Memorability of Enhanced Informational Graphics

Abstract: Design enhancements are often added to charts, signage, and infographics to help garner attention or communicate a message. Though it is argued that they may also detract user’s focus on the underlying information, prior studies have contributed evidence that visual design enhancements and even simple decorations can improve memory of visual displays. However, there is limited empirical knowledge about how the type of aesthetic enhancements infuences memory, and what informational and data elements are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…For instance, Bateman et al [4] evaluated visualisations with strong visuals against their plain version and found that embellishments enhanced long-term memorability and made the chart attractive. Li et al [26] and Pena et al, [33], who both replicated [4], made similar observations. Borkin et al [8] found that attributes such as icons, colours, human-recognisable objects, and uniqueness make people remember visualisations better.…”
Section: The Effects Of Visual Embellishmentsmentioning
confidence: 67%
See 1 more Smart Citation
“…For instance, Bateman et al [4] evaluated visualisations with strong visuals against their plain version and found that embellishments enhanced long-term memorability and made the chart attractive. Li et al [26] and Pena et al, [33], who both replicated [4], made similar observations. Borkin et al [8] found that attributes such as icons, colours, human-recognisable objects, and uniqueness make people remember visualisations better.…”
Section: The Effects Of Visual Embellishmentsmentioning
confidence: 67%
“…On the other hand, empirical research has provided evidence that contradicts this stance. For instance, embellishments were found to not hinder comprehension [4], but to make a visualisation memorable [5,26,33], engaging [3], accessible [44], and imaginable [11].…”
Section: Introductionmentioning
confidence: 99%
“…Chart type was also found to affect the time participants needed to review them as charts with visual embellishments required less time to review them [20]. This was later confirmed by Ragan et al [28], who also discovered that it was the visual embellishments that were directly related to the data which improved recall, whereas unrelated visuals had the opposite effect.…”
Section: Effects Of Data Storytellingmentioning
confidence: 77%
“…After each of these three visualization tasks, participants were presented with a post-task questionnaire containing five questions designed to test their immediate, short-term recall of the information included in the preceding visualization. To test the participants' long-term recall, participants were sent a follow-up message one week after completing the main experiment inviting them to complete the post-experiment test of their knowledge of the three visualization topics, This one-week interval between the two tests was chosen based on related work [2,20,28].…”
Section: Long-term Recall Of the Information Contained In These Visua...mentioning
confidence: 99%
“…The students replicated Bateman et al's study of how visual embellishments in charts affect comprehension and memorability [4], which has over 500 citations. Although there has been one prior replication [56] and many follow-up studies inspired by Bateman et al's work, including around the topics of visual embellishments [41,43] and memorability [7,8,32,66], the topic still remains highly debated [65]. Therefore, we replicated the study four times to further investigate this contentious topic.…”
Section: Proof-of-concept Implementationmentioning
confidence: 92%